The Role of Information Technology in Enhancing Badminton Training - Han, Hui; Wang, Han (International Journal of Social Sciences and Public Administration, 2024)
Badminton, demanding high levels of skill, sets rigorous standards for athletes’ responsiveness, precision in movement execution, and deep understanding of tactics. The integration of information technology has recently revolutionized badminton training, introducing new dimensions and methodologies for athletes and their coaches. This not only boosts training efficiency and athletic performance but also equips coaches with more scientific and comprehensive tools. As information technology evolves, its deeper and broader application in badminton training is expected to provide even more comprehensive, efficient, and scientific support, further advancing the sport’s popularity and development.